Immunohistochemical characteristics of breast cancer, increasing the risk of local reccurence after organosaving treatment - S. M. Demidov; D. A. Demidov; S. V. Sazonov; E. I. Churakova (Опухоли женской репродуктивной системы, 2018)
Objective: an immunohistochemical analysis of the characteristics of a recurrent tumor in breast cancer. Materials and methods. The statistical processing of immunohistochemical analysis’ results was performed and the most frequently encountered molecular-genetic subtypes of breast cancer with the development of local relapses were formulated. The analysis used a standard immunohistochemical panel, which is the “gold standard” for diagnostic in Russia today, and includes the expression of receptors for sex hormones (estrogen and progesterone), expression of the human epidermal growth factor HER2/neu receptor gene, and the index of proliferative activity Ki-67. The 2nd stage of the work was the evaluation of the dynamics of changes in the immunohistochemical characteristics of a recurrent tumor in comparison with the primary one. Results and conclusion. The most common local recurrence provides by triple-negative subtype of breast cancer (42 %). The changes in the immunohistochemical characteristics of a recurrent tumor in comparison with the primary one affected only the index of proliferative activity Ki-67 in the direction of its increase by 12 %.